Moulin Rouge: uma representação carinhosa da prostituição - Morgan, Juliana Michele Storch Balko (2007)
The present study has as its research object the film Moulin Rouge, directed by Baz Luhrmann and written by Luhrmann and Craig Pearce. Using the musical genre, the movie tells, in an unusual way, a story of passion, obsession and desire between a writer and a courtesan. However, more than telling a love story, the film favors the discussion of the theme of prostitution. It can be observed, from the analysis of the verbal and imagistic language, and based on a theoretical framework constituted in the intersection of Discourse Analysis, Peircean Semiotics, some theoretical aspects on the Image, and some concepts of the Cultural History, that there are two voices that constitute the discourse of the film under analysis: one is part of a collective voice, which is the generalizing discourse and embodies a social vision concerning the prostitution, constituted by a generic and pejorative enunciator; the other introduces another perspective on the world of prostitution and can be linked to a critical, taciturn and reflective enunciator. By presenting another perspective on the prostitution, the movie constitutes a counter-discourse to the common image that can be found in the society: that the world of prostitution and the people involved in it are inhumane and, for this reason, are the worst part of the society. The notions of intertextuality and world knowledge are concepts that, together with the others, contribute to a deeper and more detailed analysis of the study object, aiming at a more consistent definition of the voices that permeate the discourse.